2015
DOI: 10.1159/000367743
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Sorafenib in Patients with Transcatheter Arterial Chemoembolization (TACE) Refractory and Intermediate-Stage Hepatocellular Carcinoma

Abstract: Background and Aims: Patients with intermediate-stage hepatocellular carcinoma (HCC) refractory to transcatheter arterial chemoembolization (TACE) are considered to be candidates for sorafenib. The aim of this study was to evaluate the superiority of conversion of treatment to sorafenib on overall survival (OS) for cases refractory to TACE. Methods: This was a retrospective cohort study carried out on 497 patients with HCC who were treated with TACE therapy at our hospital between January 2008 and December 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
179
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 185 publications
(187 citation statements)
references
References 32 publications
5
179
3
Order By: Relevance
“…Two pivotal randomized phase III studies, namely the Sorafenib HCC Assessment Randomized Protocol study (7) and the Asian Pacific study (8), demonstrated that patients with unresectable HCC undergoing sorafenib therapy had significantly longer survival time compared with the placebo group. Although >5 years have elapsed since the introduction of sorafenib for the treatment of unresectable HCC in daily clinical practice, sorafenib is still regarded as first-line systemic chemotherapeutic agent for HCC (9)(10)(11). In addition, studies on prognostic factors in patients with HCC who underwent sorafenib therapy have mainly focused on tumor-associated factors, liver function, serum biomarkers and combination therapy with sorafenib (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Two pivotal randomized phase III studies, namely the Sorafenib HCC Assessment Randomized Protocol study (7) and the Asian Pacific study (8), demonstrated that patients with unresectable HCC undergoing sorafenib therapy had significantly longer survival time compared with the placebo group. Although >5 years have elapsed since the introduction of sorafenib for the treatment of unresectable HCC in daily clinical practice, sorafenib is still regarded as first-line systemic chemotherapeutic agent for HCC (9)(10)(11). In addition, studies on prognostic factors in patients with HCC who underwent sorafenib therapy have mainly focused on tumor-associated factors, liver function, serum biomarkers and combination therapy with sorafenib (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, sorafenib is the only treatment strategy available after failure of TACE [9,10] . However, in clinical practice, "progression" is not determined by development of a new small lesion, and switching from TACE to sorafenib or other therapies does not necessarily happen at this point.…”
Section: Introductionmentioning
confidence: 99%
“…The OS of patients with B1, B2, and B3 HCC according to the Kinki criteria corresponds to that of patients with HCC of BCLC stages A, B, and C. In addition, patients with BCLC substage B2 HCC, especially those with multiple HCC tumors in both lobes, are not good candidates for TACE. For patients with intermediatestage HCC (BCLC-B) who do not respond to TACE, an early switch to sorafenib therapy (rather than repeat ineffective TACE) results in a better survival benefit; therefore, early identification of patients that are refractory to TACE is crucial [14][15][16][17] . These data underscore the importance of establishing globally recognized, common criteria for identifying TACE failure/ refractory patients in order to improve the survival of HCC patients [18] .…”
Section: Hcc (Bclc-c) Patients With Intermediate-stage Hcc (Bclc-b)mentioning
confidence: 99%